PENGARUH TEKNIK NUMBERED HEADS TOGETHER TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH DASAR - Ayudhia, Alya; Sabri, Tahmid; Uliya, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The problem of this research is whether there is influence of the application of technique numbered heads together to the learning outcomes of Citizenship Education of Grade V students of State Elementary School 35 Pontianak Selatan? This study aims to prove whether or not the influence of application of technique numbered heads together on student learning outcomes. This research uses experimental method with quasi experimental design type nonequivalent control group design. The sample is a VC class of 34 students. The data collection technique used in the form of the test is multiple choice. Based on the calculation of statistical average of control class learning outcomes of 65.56 and the average of experimental class learning results of 78.26, obtained thitung = 6.580 and ttable (α = 5% and dk 34 + 33 - 2 = 65) of 1.670 , which means tcount (6,580)> ttable (1.670), then Ha is accepted. So, it can be concluded that there is influence of application of technique numbered heads together to the result of study of class V student of State Elementary School 35 Pontianak Selatan. The calculation of effect size (ES) is 1.16, meaning that learning by technique numbered heads together gives a high influence on the learning outcomes of Citizenship Education of Grade V students of SD Negeri 35 Pontianak Selatan. Keywords: Technique Numbered Heads Together, Learning Outcomes, Citizenship Education.